2022
DOI: 10.1371/journal.pone.0261481
|View full text |Cite
|
Sign up to set email alerts
|

Methylation pattern of polymorphically imprinted nc886 is not conserved across mammalia

Abstract: Background In humans, the nc886 locus is a polymorphically imprinted metastable epiallele. Periconceptional conditions have an effect on the methylation status of nc886, and further, this methylation status is associated with health outcomes in later life, in line with the Developmental Origins of Health and Disease (DOHaD) hypothesis. Animal models would offer opportunities to study the associations between periconceptional conditions, nc886 methylation status and metabolic phenotypes further. Thus, we set ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 48 publications
(89 reference statements)
0
10
0
Order By: Relevance
“…B) Schematic presentation of the nc886 gene, nc886 DMR and the CTCF-binding sites flanking the DMR. The telomeric CTCF-38 binding site has been suggested to interact with another binding site near the IL9 gene, bringing a suggested enhancer region close to the nc886 gene 1,27 . Made with BioRender.com.…”
Section: Implications For Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…B) Schematic presentation of the nc886 gene, nc886 DMR and the CTCF-binding sites flanking the DMR. The telomeric CTCF-38 binding site has been suggested to interact with another binding site near the IL9 gene, bringing a suggested enhancer region close to the nc886 gene 1,27 . Made with BioRender.com.…”
Section: Implications For Future Studiesmentioning
confidence: 99%
“…The Dicer-dependent, but Dosha-independent production of the small RNAs derived from this region was later verified by Miñones-Moyano et al and Fort et al 9,16 . However, Fort et al demonstrated that the produced small RNAs associate with Argonaute, satisfying the attributes of miRNA, and further hypothesised that the suggested recent evolutionary origin of the nc886 gene would be the reason for the poor efficiency of Dicer to produce the mature miRNAs 9,27 . This work was again followed by the work of Lee et al describing the issues arising from the classification of nc886 as miRNA and further emphasising their previous view of nc886 being distinct from pre-miRNAs 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, no animal models are available to study nc886 , as most species, including mice and rats, do not harbour the gene, and in species harbouring the nc886 gene, the locus is not polymorphically imprinted (26). Thus, we wanted to utilise available resources, the numerous existing DNA methylation datasets from humans, to gain insight on the methylation of nc886 , a unique polymorphically imprinted gene and a potential molecular mediator of DOHaD.…”
Section: Introductionmentioning
confidence: 99%
“…We found they present either intermediate methylation levels (methylation beta value 0.20-0.40; i.e., methylation level of 20-40%, in approximately 1-5% of the population) or methylation beta values >0.60 (methylation level of >60%), indicating that also the paternal allele has gained methylation in somatic tissues (in ∼0.1% of the population) [11]. The nc886 locus, flanked by two CTCF-binding sites, suggested to be important for its imprinting [14], codes for a 102nt long noncoding RNA, which might then be cleaved into miRNA-like short noncoding RNAs, although the nature of these RNAs is still widely debated [15,16].…”
mentioning
confidence: 99%
“…In vitro methods are of limited feasibility, as both carcinogenesis [13] and pluripotency induction [11] have an effect on the methylation pattern at the nc886 locus. Currently, no animal models are available to study nc886 because most species, including mice and rats, do not harbor the gene, and in species harboring the nc886 gene, the locus is not polymorphically imprinted [14]. Thus, we wanted to use available resources -the numerous existing DNA methylation datasets from humans -to gain insight on the methylation of nc886, a unique polymorphically imprinted gene and a potential molecular mediator of DOHaD.…”
mentioning
confidence: 99%